1985
DOI: 10.1002/app.1985.070300311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of matrix's type on the dynamic properties for short fiber-elastomer composite

Abstract: SynopsisThe dynamic moduli, E' and Err, and tan S for PET-CR, PET-EPDM, and PET-UR composites with unidirectional short fibers were studied as a function of temperature by using a Rheovibron. The temperature dependence of tan 6 showed three peaks for PET-elastomer composites. The peaks at the low temperature corresponded to the main dispersion of the respective matrixes and the peak at about 140°C to the adispersion of PET fiber. A small and broad peak observed at a temperature between 60 and 120°C may be caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 1 publication
2
43
0
Order By: Relevance
“…On adding more than 3% MAPP, the hard segment percentage of the wood flour was decreased and thus the tan d value increased. Ashida et al [33] reported a better interfacial adhesion between wood fiber and plastic matrix with a lower tan d value. In our study, the T b and T a peaks appeared at around À10°C and 100°C, respectively.…”
Section: Effects Of Different Plastic Matrices On the Mechanical Propmentioning
confidence: 98%
“…On adding more than 3% MAPP, the hard segment percentage of the wood flour was decreased and thus the tan d value increased. Ashida et al [33] reported a better interfacial adhesion between wood fiber and plastic matrix with a lower tan d value. In our study, the T b and T a peaks appeared at around À10°C and 100°C, respectively.…”
Section: Effects Of Different Plastic Matrices On the Mechanical Propmentioning
confidence: 98%
“…2), an impor- Ashida et al (1985) reported the relation between tanδ and interface adhesion. It can indirectly show the interface adhesion property, the smaller the loss factor tanδ, the better the interface adhesion.…”
Section: Temperature-dependent Dma Measurementsmentioning
confidence: 98%
“…The stronger the interfacial interaction is, the higher the value of parameter B [21]. Among many research works, parameter B which corrects the volume fraction of reinforcement because of the formation of a layer of immobilized interphase resulting from strong interactions at the interface is the particularly worth mentioning one conducted by Dong and Gauvin [22].…”
Section: Dynamic Mechanical Analysis Of the Compositesmentioning
confidence: 99%